2023
DOI: 10.1073/pnas.2210439120
|View full text |Cite
|
Sign up to set email alerts
|

A complete biomechanical model of Hydra contractile behaviors, from neural drive to muscle to movement

Abstract: How does neural activity drive muscles to produce behavior? The recent development of genetic lines in Hydra that allow complete calcium imaging of both neuronal and muscle activity, as well as systematic machine learning quantification of behaviors, makes this small cnidarian an ideal model system to understand and model the complete transformation from neural firing to body movements. To achieve this, we have built a neuromechanical model of Hydra ’s fluid-fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…Cnidarians emerge as informative models for neuroscience, as they have surprisingly complex neuronal circuits and enable the study of neuronal activity in complete organisms lacking a centralized nervous system 20,26,54,55 . Neuronal control of behavior in cnidarians is dispersed and control takes place in neuronal subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Cnidarians emerge as informative models for neuroscience, as they have surprisingly complex neuronal circuits and enable the study of neuronal activity in complete organisms lacking a centralized nervous system 20,26,54,55 . Neuronal control of behavior in cnidarians is dispersed and control takes place in neuronal subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…While transgenic Hydra lines exist for imaging myonemes in vivo [9], the large-scale tissue deformation of mouth opening prevents the resolution of individual myonemes (electronic supplementary material, figure S2). However, because Hydra's epitheliomuscular cells require intracellular calcium (Ca 2+ ) for contraction, we can visualize the spatio-temporal pattern of calcium in the epithelial tissue using genetically encoded Ca 2+ indicators (GCaMP6s) and thus obtain the spatio-temporal pattern of active contractile forces [10][11][12]. This allowed us to determine whether the initial active forces are localized within a specific region of the head.…”
Section: Resultsmentioning
confidence: 99%
“…Mouth opening was induced via exposure to quinine or reduced glutathione [1,14], which bind to receptors in sensory neurons [15,16]. The neurons are thought to activate epithelial cell contraction using neuropeptides [12,17,18]. Upon stimulation, variations in Ca 2+ signalling across the head were observed (electronic supplementary material, figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that both ectodermal and endodermal epithelial cells responded simultaneously to activity of the CB circuit. Since there are no nerve cell connections between the ectoderm and the endoderm (see above), they postulated (Wang et al, 2023) that the ectodermal epitheliomuscle cells activate endodermal epitheliomuscle cells directly via gap junction connections across the mesoglea (Hand and Gobel, 1972). This conclusion is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%